Comparison of bullying victimization and depression symptoms among Chinese adolescents before and after the end of the dynamic zero-COVID-19 policy: a repeated cross-sectional study - Yong Yang; Yi Lin; Feng Wang; Si Jia Wang; Jing Hui Wang; Feng Tong; Qing Hai Gong (BMC Psychiatry)
Abstract Background The COVID-19 pandemic has had a significant impact on the physical and mental health of human beings. Most adolescents in mainland of China have been infected with COVID-19 after the adjustment of the dynamic zero-COVID-19 policy. This study aims to analyze the relationship between the COVID-19 pandemic effect and depressive symptoms among adolescents in mainland China. Methods This school-based repeated cross-sectional study was conducted on students aged 11–19 years from September to October 2022 and September to October 2023 in Ningbo, Zhejiang Province, China, using a stratified cluster, multistage sampling method. Data analysis occurred from January to June 2024. Depression symptoms and bullying victimization, exclusion of cyberbullying, were assessed using the 20-item Center for Epidemiological Studies Depression Scale (CES-D) and Bully/Victim Questionnaire, respectively. Results In the first survey wave in 2022 during the dynamic zero-COVID-19 policy period in Mainland China, 10,224 participants completed the questionnaires. In wave 2 survey in 2023 which was the first year after lifting of the dynamic zero-COVID-19 policy, 11,604 participants completed the questionnaires. This resulted in a sample of 10,224 in wave 1 and 11,604 in wave 2. The mean age in wave 1 was 15.2 (SD = 1.7) and 15.1 (SD = 1.8) in wave 2. The prevalence of depression symptoms in adolescents in wave 2 was higher than in wave 1 (17.0% vs. 14.6%, P < 0.05). The prevalence of bullying victimization and types of bullying victimization in school among adolescents were higher in 2023 than in 2022. A total of 3.2% of the 2023 participants and 1.7% of the 2022 participants experienced bullying victimization in school (P < 0.05). The odds ratio of experiencing depression (CES-D Score ≧ 16) and bullying victimization in school were 1.18 (95% CI, 1.10–1.28) and 1.86 (95% CI, 1.55–2.24) times higher, respectively, in 2023 than in 2022 (P < 0.01). The mediated regression analysis revealed that after lifting of the dynamic zero-COVID-19 had a significant association with an increase in depression symptoms, which was partially mediated by bullying victimization in school (total association:β = 0.175; SE = 0.038; P < 0.001; direct association:β = 0.138; SE = 0.039; P < 0.001; indirect association: a*b = 0.037; P < 0.001; the proportion of mediation: 20.88%, P < 0.001). Conclusions The findings of this repeated cross-sectional study suggest that an increased risk of depression symptoms or bullying victimization has been associated with the COVID-19 pandemic in mainland China after lifting the dynamic zero-COVID-19 policy. In addition, bullying victimization may play a mediating role in the associations between the pandemic and depression symptoms. These findings indicated that additional support should be offered to Chinese adolescents in the period of post-pandemic COVID-19. Clinical trial number Not applicable.